2013
DOI: 10.4102/sajpsychiatry.v19i2.401
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of psycho-education on depression, hopelessness, suicidality, anxiety and substance use among basic diploma students at Kenya Medical Training College

Abstract: Objective. To determine the effectiveness of psycho-education on symptom severity in depression, hopelessness, suicidality, anxiety and risk of substance abuse among para-medical students at Kenya Medical Training College (KMTC). Methodology. A clinical trial drew experimental (N=1 181) and control (N=1 926) groups from different KMTC campuses. Self-administered questionnaires were used to collect data: the researcher-designed social demographic questionnaire

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…Findings of the T-tests and ANOVA tests conducted indicated that the psycho-education treatment led to a significant reduction in depressive symptoms among the women in the EG. These findings are similar to findings conducted by Xavier et al (2010) in South Africa, Donker et al (2009) in the USA, Dyck, Hendryx, Short, Voss, and McFarlane (2002) in Britain, and Muriungi and Ndetei (2013) and Kyobutungi, Egondi, and DEPRESSIVE DISORDERS AMONG WOMEN LIVING IN RESOURCE POOR 592 Ezeh (2010) in Kenya, which indicated that psycho-education has a positive impact on improving anxiety and depressive symptoms leading to improvements in QoL.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Findings of the T-tests and ANOVA tests conducted indicated that the psycho-education treatment led to a significant reduction in depressive symptoms among the women in the EG. These findings are similar to findings conducted by Xavier et al (2010) in South Africa, Donker et al (2009) in the USA, Dyck, Hendryx, Short, Voss, and McFarlane (2002) in Britain, and Muriungi and Ndetei (2013) and Kyobutungi, Egondi, and DEPRESSIVE DISORDERS AMONG WOMEN LIVING IN RESOURCE POOR 592 Ezeh (2010) in Kenya, which indicated that psycho-education has a positive impact on improving anxiety and depressive symptoms leading to improvements in QoL.…”
Section: Discussionsupporting
confidence: 89%
“…A sample size of 200 for both the experimental (EG, n = 100) and control group (CG, n = 100) was selected at 80% power and 30% effective size (Chan, 2003). A study conducted in Kenya showed that PE had a 30% effect on subjects with depression and a 29% effect on subjects with anxiety (Muriungi & Ndetei, 2013). In relation to this study, the PE intervention was anticipated to have a successful and clinical relevance of 30% (effect size) translating to 70% of the subjects participating in the study (Chan, 2003).…”
Section: Study Methodsmentioning
confidence: 97%
“…As mentioned earlier, there is a paucity of published research on preventive and treatment interventions. We found only one recent intervention study for suicidality, and this was not in medical students but in paramedical students (and therefore excluded from the current review) 39. Muriungi and Ndetei conducted a clinical trial across seven campuses in Kenya Medical Training College involving an experimental group (n=1181) and a control group (n=1926) to determine the effectiveness of psychoeducation on suicidality as well as other symptoms (depression, hopelessness, anxiety, and risk of substance abuse).…”
Section: Discussionmentioning
confidence: 99%
“…These tools have been validated for use in various settings involving a wide range of populations [36]. The validity and reliability of the ASSIST and AUDIT tools have been reported as good; they have been adapted for use in Kenya to investigate substance use among university students [10,39].…”
Section: Data Collection Toolsmentioning
confidence: 99%